A Team Level Perspective for Patient Adherence Promotion: Development and Initial Validation of a Short Scale for Measuring the Nursing Team Functioning - Rashkovits, Sarit; Ore, Liora (International Journal For Research In Health Sciences And Nursing, 2019)
Based on previous research that point to the need in tailoring specific solutions to the individual patient, and on the value of teamwork for quality of care, the current paper suggests a team level approach for coping with the persistent problem of insufficient patient adherence. Furthermore, a short scale for assessing the nursing team's patient adherence promotion and its initial validation are presented. As was expected, analysis of variance in a sample of 1001 nurses show that primary healthcare nursing teams, scored significantly higher than nurses from three other healthcare settings (hospitals, retirement homes, and daycare facilities). Further, a CFA with the items of this scale and the items of an established patient satisfaction scale pointed to a better fit of two factors model over one factor model. Last, in a second sample that includes 962 nurses we found an indirect effect of the nursing team's agreeable communication style on the team's patient adherence promotion that is partially mediated by team reflexivity.